Incidence and Variants of Posterior Arch Defects of the Atlas Vertebra. (10th September 2013) - Guenkel, Sebastian; Schlaepfer, Sladjana; Gordic, Sonja; Wanner, Guido A.; Simmen, Hans-Peter; Werner, Clément M. L.
Abstract : In order to describe the incidence and existing variants of congenital anomalies of the atlas vertebrae in a Caucasian population, we examined 1069 CT scans of the upper cervical spine. We found 41 cases with altered atlas vertebrae, representing 3.8% of all analyzed patients. With 83% of all found anomalies, the predominant type is characterized by a small dorsal cleft (3.2% of all patients). Rare varieties feature unilateral or bilateral dorsal arch defects, combined anterior and posterior clefts (0.2% of all patients) or total erratic atlas vertebra malformation (0.1% of all patients). Atlas arch defects are found nearly 4% at the time. Most anomalies affect the posterior arch, whereas the anterior arch or both are rarely affected. Totally irregular C1 vertebrae are extremely infrequent.